2019
DOI: 10.1002/tox.22753
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A induces apoptotic cell death via JNK/p38 activation in human nasopharyngeal carcinoma cells

Abstract: Licochalcone A is widely studied in different fields and possesses antiasthmatic, antibacterial, anti‐inflammatory, antioxidative, and anticancer properties. Its antimalignancy activity on renal, liver, lung, and oral cancer has been explored. However, limited studies have been conducted on the inhibitory effects of licochalcone A in human nasopharyngeal carcinoma cells. We determined cell viability using MTT assay. Cell cycle distribution and apoptotic cell death were measured via flow cytometry. Caspase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…Caspases-8 and -9, which correspond to the initiator caspases of each pathway, ultimately activate apoptosis through the cleavage of various cellular substrates, such as PARP, by activating down stream executioner caspases, including caspase-3 and -7 [47,48,49,50]. As shown in previous studies using human nasopharyngeal and ovarian carcinoma cells [23,33], our results demonstrate that LCA activated caspase-3 as well as caspase-8 and -9, and induced the cleavage of PARP. Therefore, we speculated that the pro-apoptotic effect of LCA in T24 cells could occur by simultaneously activating extrinsic and intrinsic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspases-8 and -9, which correspond to the initiator caspases of each pathway, ultimately activate apoptosis through the cleavage of various cellular substrates, such as PARP, by activating down stream executioner caspases, including caspase-3 and -7 [47,48,49,50]. As shown in previous studies using human nasopharyngeal and ovarian carcinoma cells [23,33], our results demonstrate that LCA activated caspase-3 as well as caspase-8 and -9, and induced the cleavage of PARP. Therefore, we speculated that the pro-apoptotic effect of LCA in T24 cells could occur by simultaneously activating extrinsic and intrinsic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LCA has been reported to inhibit cell proliferation through cell cycle arrest at the G2/M phase in various types of cancer cells, including MCF-7 breast cancer cells [7], A549 lung cancer cells [19], HepG2 human hepatoma cells [20], and U87 glioma cells [21]. In addition, the anti-cancer effects of LCA have been reported in nasopharyngeal cancer, breast cancer, cervical cancer, oral cancer, epithelial ovarian carcinoma, bladder cancer cells, and so on [7,19,20,22,23,24,25,26,27,28,29,30,31,32,33]. These anti-cancer effects have been shown to involve the death receptor (DR)-dependent extrinsic or mitochondria-dependent intrinsic pathways, which are representative apoptosis inducing pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we showed that Licochalcone A treatment induced cleaved-caspase 8 and caspase 3, but decreased the levels of Bax and cleaved-caspase 9, indicating that Licochalcone A triggers apoptosis that mediated by the extrinsic pathways in osteosarcoma cell lines. However, several literatures report that caspase 9-mediated intrinsic pathways could be induced by Licochalcone A in other cell types such as glioma stem cells [16], and nasopharyngeal carcinoma cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Licochalcone A inhibits PI3K/Akt/mTOR activation, and promotes autophagy and apoptosis in breast cancer cells [19] and cervical cancer cells [20]. Licochalcone A induces apoptotic cell death via p38 activation in human nasopharyngeal carcinoma cells [21] and head and neck squamous carcinoma cells [22]. In this study, we evaluated the potential anti-tumor effect of Licochalcone A against osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhiza uralensis is widely used in traditional Chinese medicine. Licochalcone A (LCA) is a flavonoid extracted from glycyrrhiza glabra and glycyrrhiza inflate with pharmacological activities such as anticancer, anti-inflammatory, and antioxidation properties [3][4][5]. Accumulating evidence has demonstrated that LCA exhibited anticancer activity through modulating reactive oxygen species (ROS) levels in cancer cells.…”
Section: Introductionmentioning
confidence: 99%